2015
DOI: 10.1097/iop.0000000000000024
|View full text |Cite
|
Sign up to set email alerts
|

Reticulohistiocytoma of the Orbit

Abstract: Reticulohistiocytoma is a rare, benign histiocytic proliferation of the skin or soft tissue. While ocular involvement has been documented in the past, there have been no previously reported cases of reticulohistiocytoma of the orbit. In this report, the authors describe a reticulohistiocytoma of the orbit in a middle-aged woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Since leukemic cells experience more exposure to oxidative stress intrinsically, this makes them more vulnerable to oxidative stress. Above basal level increase in oxidative stress in hematopoietic progenitor cells can cause advanced differentiation through the c-Jun N-terminal kinase (JNK) signalling pathway; further indicating that the leukaemia phenotype has a correlation with ROS levels [138,139]. In DNA bases of breast cells, purine and pyrimidine can be oxidized by ROS, forming 8-hydroxy-2 -deoxyguanosine (8-OH-dG), which is a breast cancer tissue biomarker for DNA damaged by oxidative stress.…”
Section: Redox Signalling In Cancer: Does Stat3 Maintain the Balance?mentioning
confidence: 99%
“…Since leukemic cells experience more exposure to oxidative stress intrinsically, this makes them more vulnerable to oxidative stress. Above basal level increase in oxidative stress in hematopoietic progenitor cells can cause advanced differentiation through the c-Jun N-terminal kinase (JNK) signalling pathway; further indicating that the leukaemia phenotype has a correlation with ROS levels [138,139]. In DNA bases of breast cells, purine and pyrimidine can be oxidized by ROS, forming 8-hydroxy-2 -deoxyguanosine (8-OH-dG), which is a breast cancer tissue biomarker for DNA damaged by oxidative stress.…”
Section: Redox Signalling In Cancer: Does Stat3 Maintain the Balance?mentioning
confidence: 99%
“…[1,3,5,6,9,10]. SRH is a benign, localized disease induced by cytokines that cause a rare non-neoplastic proliferation of skin histiocytes, originated from the lineage of macrophages that react to yet unknown stimuli [4,5]. Clinically, the SRH presents itself as a single, firm, yellowish or reddish, asymptomatic skin nodule, measuring 0.5 to 2.0 centimeters, but usually smaller than one centimeter [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry shows positivity for CD68 and CD163 and, in some cases, also for alpha-1-antitrypsin and lysozyme. The negativity of markers such as CD1a and S100 is essential for the differential diagnosis and exclusion of other histiocytosis [4,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 A study of 44 cases reported that these lesions tend to occur at several sites including the head and neck, trunk, arms, and legs, 1 although facial involvement is rare in solitary RH and more common in multicentric reticulohistiocytosis. Rare locations include the penis, 3 orbit, 4 and eyelid. 5 In contrast to multicentric reticulohistiocytosis, which lies in the same spectrum of disease, solitary RH has not been associated with systemic disease or malignancy.…”
Section: Introductionmentioning
confidence: 99%